Novel Antineuronal Autoantibodies With Somatodendritic Staining Pattern in a Patient With Autoimmune Psychosis - Endres, Dominique; Rauer, Sebastian; Pschibul, Alexander; Süß, Patrick; Venhoff, Nils; Runge, Kimon; Feige, Bernd; Denzel, Dominik; Nickel, Kathrin; Schweizer, Tina; Maier, Simon; Egger, Karl; et al. (Frontiers in Psychiatry, 2020)
Background: Autoimmune encephalitis, such as anti-NMDA-receptor encephalitis, typically presenting with subacute onset of neuropsychiatric symptoms, can be detected by antineuronal autoantibodies or inflammatory changes in the cerebrospinal fluid (CSF), pathological alterations in electroencephalography (EEG), magnetic resonance imaging (MRI), or [18F]fluorodeoxyglucose positron emission tomography (FDG PET). For patients with predominant psychotic symptoms, the term autoimmune psychosis was proposed. Here, the authors present the case of a patient with probable autoimmune psychosis associated with unknown antineuronal antibodies. Case presentation: A 18-year-old male patient with preexisting autism spectrum disorder developed a severe catatonic syndrome over 2.5 years. The MRI showed normal findings, the EEG depicted intermittent slowing, and the independent component analyses showed additional sharp spikes. However, FDG PET, the basic laboratory analysis and testing of the serum/CSF for well-characterized antineuronal autoantibodies were unsuspicious. The serum and CSF “tissue-based assay” using indirect immunofluorescence on unfixed murine brain tissue revealed antineuronal autoantibodies against an unknown epitope in granule cells in the cerebellum and to neurites of hippocampal interneurons with a somatodendritic staining pattern. The immunosuppressive treatment with high-dose glucocorticoids, plasma exchange, and rituximab led to partial improvement. Conclusion: The patient probably suffered from autoantibody-associated autoimmune psychosis. The special features of the case were that the patient 1) presented with mostly inconspicuous basic diagnostics, except for the altered EEG in combination with the detection of CSF autoantibodies directed against a currently unknown epitope, 2) experienced an isolated and long-lasting psychotic course, and 3) had pre-existing autism spectrum disorder. The detection of a probable autoimmune pathophysiology in such cases seems important, as it offers new and more causal immunosuppressive treatment alternatives.